Konsekuensi terhadap Perekonomian Indonesia Akibat Invasi Rusia ke Ukraina - Iswah, Iswahyudi; Millatipuan, Meika Arifatull (Pascasarjana Universitas Sultan Ageng Tirtayas, 2024)
This study intends to examine the impact of the conflict between Russia and Ukraine on the Indonesian economy. The conceptual framework of this research refers to Peterson's theory in his research. There are five indicators in this study, namely supply chain, banking system, economic growth, stock markets, and rising inflation. The result is that the supply chain, economic growth, the Indonesian stock market and inflation are adversely affected by the conflict. Meanwhile, the banking system was not adversely affected, because the Indonesian side carefully did not make a decision to impose sanctions or prefer a neutral policy (non-block). This makes Russia not consider Indonesia as a target for the cyber banking system, and maintain good cooperation in country business.